Advancing Sustainability and Social Justice: Developing Sustainability Societies for Muslim Women - Datta, Rimmi; Mete, Jayanta (FISIP UIN Sunan Gunung Djati Bandung, 2024)
Research Problem: Muslim women in developing countries face unique challenges influenced by cultural, religious, and socioeconomic factors. These challenges impact their ability to participate in sustainable development initiatives, despite Islamic teachings emphasizing environmental stewardship, social justice, and equitable economic opportunities. Research Purposes: This paper explores the concept of